TSNsched: automated schedule generation for time sensitive networking - Santos, Aellison Cassimiro Teixeira dos (2020)
Time Sensitive Networking (TSN) is a set of standards enabling high performance de terministic communication using time scheduling. Due to the size of industrial networks, configuring TSN networks is challenging to be done manually. We present TSNsched, a tool for automatic generation of schedules for TSN. TSNsched takes as input the logical topology of a network, expressed as flows, and outputs schedules for TSN switches by using an SMT-solver. The generated schedule guarantees the desired network performance (specified in terms of latency and jitter), if such schedules exist. TSNsched supports unicast and multicast flows, such as, in Publish/Subscribe networks; can combine existing variants of TSN scheduling problems, and reason about the best-effort and priority TSN traffic. TSNsched can be run as a standalone tool and also allows rapid prototyping with the available JAVA API. We evaluate TSNsched on a number of realistic-size network topologies. TSNsched can generate high performance schedules, with average latency less than 1000μs, and average jitter less than 20μs, for TSN networks, with up to 138 subscribers and up to 10 multicast flows.